Heat Shock Proteins Can Be Surrogate Autoantigens for Induction of Antigen Specific Therapeutic Tolerance in Rheumatoid Arthritis - van Eden, Willem; Jansen, Manon A. A.; Ludwig, Irene S.; Leufkens, Paul; van der Goes, Marlies C.; van Laar, Jacob M.; Broere, Femke (Frontiers in Immunology, 2019)
Technologies that enable induction of therapeutic tolerance may revolutionize the treatment of autoimmune diseases by their supposed potential to induce drug-free and lasting disease remission. In combination with diagnostic tests that screen for individuals at risk, these approaches may offer chances to halt disease before serious damage in the tissues can occur. In fact, for healthy individuals at risk, this could lead to a preventive form of vaccination. For therapeutic tolerance to re-instate natural self-tolerance it seems essential to induce tolerance for the critical autoantigens involved in disease. However, for most autoimmune diseases such antigens are poorly defined. This is the case for both disease inciting autoantigens and antigens that become involved through epitope spreading. A possible source of surrogate auto-antigens expressed in tissues during inflammation are heat shock proteins (HSP) or stress proteins. In this mini-review we discuss unique characteristics of HSP which provide them with the capacity to inhibit inflammatory processes. Various studies have shown that epitopes of HSP60 and HSP70 molecules can function as vaccines to downregulate a variety of autoimmune inflammatory diseases. Currently, several research groups are developing cell therapies with the intention to reach therapeutic tolerance. In this review, in which we are proposing to ex vivo load tolerant dendritic cells with a Treg inducing HSP70 derived peptide called B29, we are discussing the chances to develop this as an autologous tolDC therapeutic tolerance therapy for rheumatoid arthritis.